Asas Legalitas Dalam Hukum Positif Perspektif Hukum Pidana Islam - Muadz Abdul Aziiz; Muhammad Azaria Kanigara; Puspa Puspita Anugrah; Putri Sansadila Yustisia; Deden Najmudin (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to understand the definition, similarities and differences in the principle of legality in positive criminal law and Islamic criminal law. The method used is normative juridical through literature review, and allows for systematic analysis of legal materials. The principle of legality in positive criminal law protects society by limiting the authority of the authorities, while in Islamic criminal law, the aim is to glorify humans through protecting offspring, property, reason, soul and religion. There are similarities in the understanding of the principle of legality and interpretation theory, although there are differences, for example analogies are permitted in Islamic criminal law, but not in positive criminal law.